Implementasi Kebijakan Penataan dan Pembinaan Pasar Tradisional, Pusat Perbelanjaan dan Toko Modern Di Kota Palembang - Basri, Hasan; Mahdiana, Yana; Saswita, Yanuar (@-Publik: Jurnal Administrasi Publik, 2023)
Implementation of policies for the Arrangement and Development of Traditional Markets, Shopping Centers and Modern Stores is a planning process in an effort to improve order, order and security, and is a process carried out to change individual behavior and shape their personality, so that what they aspire to can be achieved as expected. This research aims to analyze the implementation of policies for the arrangement and development of traditional markets, shopping centers and modern shops in the city of Palembang. Data collection techniques use observation, interviews and documentation, while the analysis technique used in this research is qualitative data analysis techniques. This research shows that the implementation of guidance, supervision and evaluation of the management of Shopping Centers and Modern Stores is carried out by the Mayor. Coaching takes the form of creating a management system for training human resources, consultation, facilitating cooperation, while supervision is carried out on the business management of Shopping Centers and Modern Stores. The Mayor coordinates with the Governor of South Sumatra and the Minister of Trade of the Republic of Indonesia to: Anticipate possible problems arising in the management of shopping centers and modern stores; and Taking the necessary steps to resolve problems resulting from the establishment of modern shopping centers and shops. To improve the weaknesses found in the Implementation of Policies for the Arrangement and Development of Traditional Markets, Shopping Centers and Modern Stores in the City of Palembang, it is necessary to increase the use of verbal communication from subordinates to superiors, using written communication so that subordinates can provide feedback/responses to messages conveyed by superiors. Steps that must be taken by the Palembang City government, especially the Department of Industry and Trade to develop traditional markets include empowering the modern market itself which is carried out by the local city government.